MO230: De Novo Double Glomerulopathy (Membranous Nephropathy, Mn and Collapsing Focal Segmental Glomerulosclerosis, CFSGS) Associated to Positive Myeloperoxidase-O (MPO) Antibody Following Pfizer-Biontech MRNA Vaccination Covid 19. (3rd May 2022) - Marega, Alessandra; Pizzolitto, Stefano; Pian, Martina; Biasi, Caterina; Giacomini, Alice; Bertoni, Martina; Romano, Giulio; Boscutti, Giuliano
Abstract: BACKGROUND AND AIMS: In the COVID 19 pandemic era, anti SARS-CoV-2 vaccination showed high efficacy at preventing the infection and its most severe complications. The aim of this report is to describe an unusual double glomerulopathy related to anti SARS-CoV-2 vaccination and the good results obtained with the immunosoppressive treatment. METHOD: An 80-year-old caucasian woman developed a nephrotic syndrome, progressive renal insufficiency and microhematuria. The patient presented a medical history of thrombocytopenic purpura treated and resolved by steroids in 2013, hypothyroidism, hypertension, ischaemic heart disease treated with surgical bypass in 2019 and pacemaker in 2020 for atrial ventricular block. Due to pandemic COVID 19 status, she received two doses of the Pfizer BioNTech mRNA COVID-19 vaccine in March 2021. Two weeks after the second dose her weight increased of 23 kg. The family physician added furosemide to her therapy for generalized edema with no diuretic effect. In April, creatinine was 1.38 mg/dL ( versus 0.8 mg/dL 1 year before); urinalysis showed proteinuria (300 mg/dL) and microscopic hematuria; serum total cholesterol level was 218 mg/dL and triglycerides 178 mg/dL; then it was suggested to increase the doses of furosemide. In May 2021, creatinine resulted 2 mg/dL, serum albumin 2 g/dL, and urinalysis confirmed proteinuria and microscopic hematuria; proteinuria was 10 g/day. Abdomen ultrasound showed normal liver, kidneys and spleen, not ascites. Lower limb eco-Doppler showed right superficial femoral artery stenosis of 60% and absence of venous thrombosis. The physical examination evidenced anasarca. The patients were admitted to the nephrology unit; hepatitis B surface antigen, hepatitis C antibody and human immunodeficiency virus antigen and antibody were negative. Both complement C3 and C4 levels resulted within the normal range. Cryoglobulins were absent. Urinary Bence Jones, antinuclear antibody (ANA), anti-extractable nuclear antigen (ENA), anti-double stranded DNA (nDNA) antibodies were negative. Antineutrophil cytoplasm antibodies (ANCA) were 1:2560 with Perinuclear pattern and anti-MPO positivity (716 UA/mL); anti-proteinase-3 antibodies (PR3) were negative. Anti-phosholipase A2 receptor antibody (PLA2R Ab) was positive with high titre. A kidney biopsy was performed showing a double nephropathy: a focal segmental glomerulosclerosis (FSGS) with some collapsing features, superimposed on membranous glomerulonephritis (Fig. 1 ). RESULTS: We started the Ponticelli regimen (alternate months steroids and cyclophosphamide). After the first month of therapy, blood tests revealed creatinine 1.7 mg/dL, haemoglobin 11.7 g/dL; serum albumin 2.7 g/dL and urinalysis without microscopic haematuria. At the third month of therapy, the patient developed atrial fibrillation and started anticoagulation; blood tests were as follows: creatinine 1.1 mg/dL, serum albumin 3.0 g/dL, Ab anti-MPO 7 UA/mL and PLA2R Ab was absent. A left ocular, frontal and parietal herpes zoster induced a short discontinuation of therapy and responded well to Acyclovir; then we concluded the fourth month of therapy. At the fifth month, a SARS CoV 2 RT PCR unexpectedly resulted positive; the patient remained asymptomatic, but we stopped definitively the therapy. One month later, blood tests showed: creatinine 1 mg/dL, serum albumin 4 g/dL, proteinuria 0.7 g/die, MPO 2 UA/mL and PLA2R Ab absent. CONCLUSION: To our knowledge, this is the first case of nephrotic sindrome secondary to a de novo MN and FSGS, associated with positive MPO antibody, following Pfizer–BioNTech mRNA vaccination COVID 19; the patient responded well to immunosoppression going in remission and regaining renal function.